2009
DOI: 10.1080/10641950802601203
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Maternal Cardiovascular Adaptation to Spontaneous and Assisted Conception Pregnancies

Abstract: Ovum donation pregnancies are associated with higher BP in early pregnancy, whilst multiple pregnancies are associated with higher BP, FS and LV mass in later pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
1
3
1
1
Order By: Relevance
“…Increased SV, as a result of an increased blood volume, was previously believed to be the main determinant of the increase in  in the first trimester 4 8 32. However, the present results showed only a small contribution of SV to the observed increase in 6 9. This may be result of substantial vasodilation of the renal and systemic circulation combined with an increased capacity and filling state of the venous compartment accommodating the increased blood volume 33 34.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Increased SV, as a result of an increased blood volume, was previously believed to be the main determinant of the increase in  in the first trimester 4 8 32. However, the present results showed only a small contribution of SV to the observed increase in 6 9. This may be result of substantial vasodilation of the renal and systemic circulation combined with an increased capacity and filling state of the venous compartment accommodating the increased blood volume 33 34.…”
Section: Discussioncontrasting
confidence: 63%
“…Four studies reported multiple datasets within one of the predetermined gestational age ranges for example, data at week 8 and week 10, both eligible to be included for first trimester (6–13 weeks) analyses 4 6 9 26. In all cases, the data were not included within the meta-analysis for that predetermined gestational age in order to avoid statistical bias that would arise from inclusion of multiple datasets from an individual study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean arterial pressure (MAP) is slightly higher in both early and late forms of preeclampsia, before 20 weeks and began to increase at ~20‐ and ~32‐weeks in early and late forms of preeclampsia, respectively (Borghi et al, 2000; Bosio et al, 1999; Browne et al, 2011a; Buddeberg et al, 2018; Çağlar et al, 2016; Chapman et al, 1998; Clapp III & Capeless, 1997; Clark et al, 1989; Cong et al, 2015; Cornette et al, 2011; Del Bene et al, 2001; Dennis et al, 2012; Desai et al, 2004; D'Silva et al, 2013; Duvekot et al, 1995; Easterling et al, 1990; Estensen et al, 2012; Ferrazzi et al, 2018; Flo et al, 2010; Foo et al, 2018; Geva et al, 1997; Gilson et al, 1997; Gyselaers et al, 2014; Hennessy et al, 1996; Jia et al, 2010; Khalil et al, 2014; Kuleva et al, 2011; Lof et al, 2005; Mabie et al, 1994; Mahendru et al, 2014; Mahendru et al, 2017; Meah et al, 2016; Melchiorre et al, 2011; Melchiorre et al, 2013; Melchiorre, Sutherland, Liberati, & Thilaganathan, 2012; Melchiorre, Sutherland, Watt‐Coote, et al, 2012; Mesa et al, 1999; Moertl et al, 2012; Mone et al, 1996; Nevo et al, 2010; Novelli et al, 2012; Ogueh et al, 2009; Perry et al, 2019; Perry et al, 2020; Poppas et al, 1997; Rang et al, 2007; Rang et al, 2008; Robb et al, 2009; Robson et al, 1989; San‐Frutos et al, 2005; Savu et al, 2012; Schannwell et al, 2002; Sengupta et al, …”
Section: Illustrative Simulationsmentioning
confidence: 99%
“…Cornette et al, 2011;Del Bene et al, 2001;Dennis et al, 2012;Desai et al, 2004;D'Silva et al, 2013;Duvekot et al, 1995;Easterling et al, 1990;Estensen et al, 2012;Ferrazzi et al, 2018;Flo et al, 2010;Foo et al, 2018;Geva et al, 1997;Gilson et al, 1997;Gyselaers et al, 2014;Hennessy et al, 1996;Jia et al, 2010;Khalil et al, 2014;Kuleva et al, 2011;Lof et al, 2005;Mabie et al, 1994;Mahendru et al, 2014;Mahendru et al, 2017;Meah et al, 2016;Melchiorre et al, 2011;Melchiorre et al, 2013;Melchiorre, Sutherland, Watt-Coote, et al, 2012;Mesa et al, 1999;Moertl et al, 2012;Mone et al, 1996;Nevo et al, 2010;Novelli et al, 2012;Ogueh et al, 2009;Perry et al, 2019;Perry et al, 2020;Poppas et al, 1997;Rang et al, 2007;Rang et al, 2008;Robb et al, 2009;Robson et al, 1989;San- Frutos et al, 2005;Savu et al, 2012;…”
unclassified